Perfecting the Administrative Solution to Labour Disputes. British Columbia Experiment - Joseph, Philip (Relations industrielles / Industrial Relations, 1983)
An analysis of the unique nature of the administrative solution to labour disputes in British Columbia experience, with particular reference to section 33 of the Labour Code.